1998
DOI: 10.1021/ja974010k
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Spinosyn A. 2. Degradation Studies Involving the Pure Factor and Its Complete Reconstitution

Abstract: A total synthesis of natural levorotatory spinosyn A (1) has been achieved. The first objective, to confirm the absolute configurational assignment of tricyclic ketone 2 prepared earlier, was accomplished by oxidative degradation of the macrocyclic lactone ring in 1. The route began with the implementation of a four-step one-pot process that resulted in the efficient conversion of 6 into 18. A combination of periodate cleavage and peracid oxidation events then led to 2. In the reconstruction phase, a Pd-cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…28 Total syntheses of the natural (À)-enantiomer have been subsequently accomplished. 29,30 In addition, studies analyzing methodology for the synthesis of both the natural product and certain analogs have been conducted. [31][32][33][34] FERMENTATION-DERIVED ANALOGS Numerous structurally related compounds from various spinosyn fermentations have now been isolated and identified.…”
Section: Structure and Synthesismentioning
confidence: 99%
“…28 Total syntheses of the natural (À)-enantiomer have been subsequently accomplished. 29,30 In addition, studies analyzing methodology for the synthesis of both the natural product and certain analogs have been conducted. [31][32][33][34] FERMENTATION-DERIVED ANALOGS Numerous structurally related compounds from various spinosyn fermentations have now been isolated and identified.…”
Section: Structure and Synthesismentioning
confidence: 99%
“…Kirst et al (3) suggested that the biosynthesis of spinosyn A may involve a transannular Diels-Alder (TDA) (13) reaction of a macrocyclic pentaene to form the C(4)OC (12) and C(7)OC (11) bonds (see 4 3 3; Scheme 1). Kirst also suggested that a transannular cyclization of a 1,3-dicarbonyl nucleophile may generate the C(3)OC (14) bond (3).…”
Section: Synthetic Strategymentioning
confidence: 99%
“…Finally, removal of the PMB group with 2,3-dichloro-4,5-dicyano-1,4-benzoquinone (DDQ) afforded the spinosyn A pseudoaglycon 28, which was identical in all respects to natural 28. Because the published syntheses of (Ϫ)-spinosyn A (1) by Paquette et al (10,11) and (ϩ)-spinosyn A by Evans and Black (9) proceed by way of the pseudoaglycon 28 (or ent-28 in the case of Evans and Black), this synthesis of 28 constitutes a formal synthesis of (Ϫ)-spinosyn A (1).…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations